Interaction of Active Species in R (He, Ne, Ar)-Molecular Gas Plasmas - Ricard, André; Amorim, Jayr; Touzeau, Michel (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
In high pressure, He glows discharges and the 3-body reactions of He (23 S) metastable atoms and He+ ions with He and N2 are in competition to excite the \(N_2^+\) (B,0) radiative states. With [He+] < 1010 cm-3 and [He (23 S)] ~ 1012 cm 3 as found in a DC glow discharge, it is estimated that the 3-body reaction He(23 S) + He + N2 was the dominant process. By using the actinometry method with Ar and Ne impurity in N2 - H2DC glow discharge at 5 Torr, it was found in the negative glow of the DC discharge a small increase of all N2 vibrational states and cathode temperatures as a few H2 was introduced into N2. Finally, it discusses the methods to obtain the plasma gas temperatures from the rotational structures of N2, CN, OH, H2 and O2 radiative states.